A Review of the Literature: The Situation of Continuing Nursing Education in Iran - Mohsen Shahriari (Journal of Global Pharma Technology, 2017)
Background: Continuing nursing education is one of the ways of improving the quality of patient care. So, the evaluation of these programs will be very important. The present study has been designed and implemented with the aim of investigating the situation of continuing nursing education in Iran. Materials and methods: This study was a narrative review in a matrix approach that has been done by studying 16 articles in English and Persian. The search was performed in SID, IRANMEDEX, PUBMED, PREQUEST, CINHAL and Google Scholar data bases. Articles’ screening was performed in 4 stages. Results: In 3 areas of needs’ assessment and planning, implementation of continuing education plans and overall evaluation of programs, these studies evaluated their research environments. Most studies estimated general continuing nursing education in moderate level. Conclusions: Making changes in three areas of planning, implementation and evaluation with the participation of nurses seems to be necessary. Keywords: Continuing Education, Nurses, Review Study, Iran